IMPLEMENTASI PENDIDIKAN AGAMA ISLAM DALAM PEMANFAATAN PLATFORM YOUTUBE SEBAGAI MEDIA PEMBELAJARAN DI MADRASAH TSANAWIYAH NURUL HIDAYAH KOTA JAMBI - Rahmawati, Widia; Fadly Habibi, M. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the gap between the availability of adequate digital infrastructure and the still-suboptimal use of the YouTube platform in Islamic Religious Education (PAI) learning at MTs Nurul Hidayah Jambi City. This study aims to examine the implementation of PAI through the use of YouTube as a learning medium, to identify supporting and inhibiting factors, and to assess its effectiveness. This research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving the school principal, PAI teachers, and students as research subjects. The findings indicate that the use of YouTube in PAI learning at MTs Nurul Hidayah remains incidental and has not been systematically integrated into the learning design. Supporting factors include the availability of digital infrastructure, students' ownership of smartphones, and students' positive responses toward video-based learning. Inhibiting factors include the absence of a specific PAI digitalization program and the uneven basic ability of students in reading the Qur'an. Overall, the use of YouTube was found to enhance students' interest, attention, and understanding of PAI subject matter compared to conventional methods.